1983
DOI: 10.1121/1.389562
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic shadowing by an isolated seamount

Abstract: Acoustic shadowing by an isolated seamount has been studied by examining the multipath propagation measurements obtained in a shot run that passed over the seamount peak. Source depths of 24 and 196 m were used in the experiment. In the acoustic shadow, the propagation loss for the shallow 24-m shots increased by 10-15 dB over the loss expected in the absence of the seamount. Examination of the pressure-time history for shots deployed in the shadowing region revealed that the signals consisted of two component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Both forward and backscattering for a seamount have been studied by several investigators theoretically and experimentally including models usually with SUS, or explosive sources or piezoelectric ones for the models. [1,2,3,4,5,6] BASSEX was unique since it uses modulated signals as well as an array which permitted pulse compression for high resolution of arrival times and a array for the multipath. In addition, the array has the ability to resolve the direction of arrival which is roughly 2 degrees at broadside and 15 at endfire.…”
Section: Long Term Goalsmentioning
confidence: 99%
“…Both forward and backscattering for a seamount have been studied by several investigators theoretically and experimentally including models usually with SUS, or explosive sources or piezoelectric ones for the models. [1,2,3,4,5,6] BASSEX was unique since it uses modulated signals as well as an array which permitted pulse compression for high resolution of arrival times and a array for the multipath. In addition, the array has the ability to resolve the direction of arrival which is roughly 2 degrees at broadside and 15 at endfire.…”
Section: Long Term Goalsmentioning
confidence: 99%
“…Since the effects of seamounts are complex and the efficiency of numerical methods is usually low, previous studies on the sound propagation of seamounts mostly used 2D or N×2D models. With the deepening of ocean acoustics research, the focus gradually shifted to research about the 3D sound propagation phenomena of seamounts [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out near Dickins Seamount in the northeast Pacific Ocean in 1975 [4,5] using explosive shots and CW sources. The results showed that the TL increased up to about 15 dB because the deep refracted waves would be blocked by the seamount, and the shadowing loss behind seamount was an f 1/2 dependence at frequencies greater than 50 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment showed that the peak pressure levels recorded at Wake were as much as 35 dB below those at Midway and the spectral energy density ratio between Wake and Midway was frequently independent. Another experiment was carried out over the Dickins Seamount in the northeast Pacific ocean in 1975 [6,7] by using both explosive shots and CW sources. The results showed that the increased TL was up to 15 dB for the shallow source in which all deep refracted waves could be blocked by the seamount and the shadowing loss behind the seamount was an 𝑓 1/2 dependence at frequencies larger than 50 Hz.…”
mentioning
confidence: 99%